Which expression is equivalent to 6x+8 PLZZZZZZZZZZZZ HEWLPPP!
2 answers:
Answer:
So the second one
Step-by-step explanation:
2(3x-4) =6x-8
2(3x+4)
=6x+8 2x3=6 2x4=8
2(4x+6)
=8x+12
2(3x+8)=6x+16
<h3>✽ - - - - - - - - - - - - - - - ~Hello There!~ - - - - - - - - - - - - - - - ✽</h3>
➷ Expand them all to see if you get the expression:
2(3x - 4) ==> 6x - 8
2(3x + 4) ==> 6x + 8
2(4x + 6) ==> 8x + 12
2(3x + 8) ==> 6x + 16
As you can see, the correct option is B. 2(3x + 4)
<h3><u>
✽</u></h3>
➶ Hope This Helps You!
➶ Good Luck (:
➶ Have A Great Day ^-^
↬ <u>ʜᴀɴɴᴀʜ</u> ♡
You might be interested in
Total amount of money = amount Jenny receives + amount Bailey receives
$30 = 2j + j
30 = 3j
j = $10
To analyze [insert whatever box and whisker plot does] and compare.
Answer:
13.4
Step-by-step explanation:
To find perimeter, add all four sides.
Sorry, It seems like i dont have a sign to look of of, I can help you when you post that though!